2017
DOI: 10.5324/cjcr.v0i30.2190
|View full text |Cite
|
Sign up to set email alerts
|

Chironomus strenzkei Fittkau, 1968 is a junior synonym of C. striatipennis Kieffer, 1910

Abstract: Two species of Chironomus with essentially identical adult wing patterns, C. strenzkei and C. striatipennis, have been reported from Brazil. Specimens were collected from the same region in the Manaus area some 50 years apart. Morphological, cytological and DNA Barcode comparisons all confirm that these two species are inseparable on any of the characteristics studied. Moreover, for the mitochondrial COI region investigated, the sequences are completely identical, and polytene chromosome banding patterns are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Chironomus pilicornis can be identified according to the shape of the genitalia, which are very similar to those of Chironomus (Chironomus) plumosus (Linnaeus, 1758) (Martin, 2017;Wülker, 1996). AAE9024), which confirms their unclear taxonomic status.…”
Section: The Genus Chironomusmentioning
confidence: 57%
See 1 more Smart Citation
“…Chironomus pilicornis can be identified according to the shape of the genitalia, which are very similar to those of Chironomus (Chironomus) plumosus (Linnaeus, 1758) (Martin, 2017;Wülker, 1996). AAE9024), which confirms their unclear taxonomic status.…”
Section: The Genus Chironomusmentioning
confidence: 57%
“…Chironomus pilicornis (Fabricius, 1787) has a similar north‐eastern distribution. Chironomus pilicornis can be identified according to the shape of the genitalia, which are very similar to those of Chironomus (Chironomus) plumosus (Linnaeus, 1758) (Martin, 2017; Wülker, 1996). The barcode data available in BOLD for C .…”
Section: Taxonomic Remarks On European Chironomidae Derived From Morp...mentioning
confidence: 99%
“…Chironomus striatipennis Kieffer (Diptera: Chironomidae) is widely distributed in Holarctic, Oriental and Neotropical regions; its larvae frequently present in oligotrophic to eutrophic freshwater, such as lakes, swamps, rivers, sewage ditches, fish ponds and rice fields; it is regarded as an alien species to America derived from Asia by unintentional human transport (Al-Shami et al, 2012;Amora et al, 2015;Martin, 2017) (Figure 1). C. striatipennis is widespread in China (Wang et al, 2020); we had ever found its larvae infected municipal water systems in several cities in South China.…”
Section: Introductionmentioning
confidence: 99%